STRATEGIES TO REDUCE ROAD ACCIDENTS PARTICIPATORY FORM OF COMMUNICATION NETWORK HEAlTH REGION 8, MINISTY OF PUBLIC HEALTH - Pitupong, Apiwat; Sanposh, Krittikar; Thurisut, Thanakrit (Journal of Social Science and Cultural, 2024)
This research is a mixed methods research were 1) studying the conditions and problems of reducing road accidents with the participation of community networks, 2) determining strategies for reducing road accidents with the participation of community networks, and 3) conducting trial use. The participatory road accident reduction strategy of the 8th Health District Community Qualitative research, target group of 12 qualified persons and 30 experts, purposively selected. The research tools were structured interview forms and meeting minutes, analyzing data in terms of content. Quantitative research, sample group of 400 people, using multi - stage random sampling methods and sample group of 30 people, purposively selected. The research tools were a 5 - level rating questionnaire and a knowledge tests utilizing statistics such as frequency, percentage, mean, and standard deviation, as well as t - test paired two - sample and content analysis. Research results 1) Conditions of the problem of reducing road accidents Participatory model of the community network, Health Region 8, Ministry of Public Health, found that road accidents are related to the behavior of car users, road conditions, vehicles, and the environment. Community participation is important in solving problems. The main factors are speeding, cutting in front, and drunk driving. Proper preventive measures are required. 2) Indicators and results of the evaluation of the participatory road accident reduction strategy of the community network aspect developed in terms of appropriateness, feasibility aspect, usefulness aspect and correctness aspect terms of suitability, feasibility, usefulness, and accuracy, all aspects were rated at the highest level on average. 3) The results of using the strategy found that the average knowledge score of the trainees after using the road accident reduction strategy with participation of the community network of Health Area 8 was significantly higher than before use at the 0.01 level.